BEYOND BOUNDARIES: A CRITICAL REVIEW OF INNOVATIVE STRATEGIES IN THE GLOBAL BATTLE AGAINST INFECTIOUS DISEASES - Abdullah Hussain abdullah algofainah, Ali Naser Saleh Amodan, Nasser Ojian Saeed Alrizq, Salem Abdullah Salem Alyami, Mohammed Obaiyn S Almansour , Mohammed Ali Husain Almansour , Yahya Hamad Al Haydar , Hadi Hamad Al Haydar (Chelonian Research Foundation, 2023)
In the face of ever-evolving infectious diseases, the global health community is constantly seeking innovative strategies to combat these pervasive threats. This critical review examines the latest advancements and collaborative efforts that transcend traditional boundaries in the fight against infectious diseases. We explore the impact of cutting-edge technologies in disease surveillance, the pivotal role of vaccination in prevention, and the promising avenues of personalized medicine in treatment. The review also highlights the significance of cross-sector collaboration, integrating efforts from governments, private sectors, and non-profit organizations worldwide. Despite the progress, the article identifies key challenges, including financial constraints, logistical hurdles, and ethical dilemmas, that impede the global response to infectious diseases. Looking forward, we discuss the potential of artificial intelligence and machine learning in revolutionizing disease prediction and response strategies, emphasizing the need for sustainable health systems and continuous innovation. This comprehensive analysis aims to provide insights into the multifaceted approach required to effectively manage and mitigate the threat of infectious diseases in the contemporary world. Keywords: Global Health, Infectious Diseases, Innovative Strategies, Disease Surveillance, Vaccination, Personalized Medicine, Cross-sector Collaboration, Artificial Intelligence, Sustainable Health Systems, Ethical Considerations